The meaning of the oral tradition Penganjak Kuda Sitajur in the accompaniment of kulcapi within the Karo community - Sinulingga, Ramanta; Purba, Mauly; Ginting, Pulumun Peterus (Talenta Publisher, 2026)
The study examines the oral tradition of